ACCORD DU PARTICIPE PASSÉ AVEC L'AUXILIAIRE "AVOIR" («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article examines the agreement of the past participle with the auxiliary verb "avoir" in French grammar in person and number.
Keywords: Auxiliary